Cold environments and health: proteomic analysis of health impacts - Song Hongquan; Zhang Rui; Lu Zixin; Jiao Xiaohui; Yan Jiaqun (Frigid Zone Medicine)
Cold temperatures cause blood vessels to constrict, shallow breathing, and slight thickening of the blood. Working in extremely cold environments can have negative effects on health, yet there are currently no effective biomarkers to monitor these health conditions. Proteins are important intermediate phenotypes that can provide a theoretical basis for understanding disease pathophysiology. Proteins in the circulatory system reflect the physiological status of individuals, and plasma proteins have significant potential as biomarkers for various health conditions.